The BDS checklist as measure of illness severity: a cross-sectional cohort study in the Danish general population, primary care and specialised setting. Issue 12 (10th December 2020) - Petersen, Marie Weinreich; Rosendal, Marianne; Ørnbøl, Eva; Fink, Per; Jørgensen, Torben; Dantoft, Thomas Meinertz; Schröder, Andreas
Abstract : Objective: The bodily distress syndrome (BDS) checklist has proven to be useful in the diagnostic categorisation and as screening tool for functional somatic disorders (FSD). This study aims to investigate whether the BDS checklist total sum score (0–100) can be used as a measure of physical symptom burden and FSD illness severity. Design: Cross-sectional. Setting: Danish general population, primary care and specialised clinical setting. Participants: A general population cohort (n=9656), a primary care cohort (n=2480) and a cohort of patients with multiorgan BDS from specialised clinical setting (n=492). Outcome measures: All data were self-reported. Physical symptoms were measured with the 25-item BDS checklist. Overall self-perceived health was measured with one item from the 36-item Short-Form Health Survey (SF-36). Physical functioning was measured with an aggregate score of four items from the SF-36/SF-12 scales 'physical functioning', 'bodily pain' and 'vitality'. Emotional distress was measured with the mental distress subscale (SCL-8) from the Danish version of the Hopkins Symptom Checklist-90. Illness worry was measured with the six-item Whiteley Index. Results: For all cohorts, bifactor models established that despite some multidimensionality the total sum score of the BDS checklist adequately reflected physical symptom burden and illness severity. The BDS checklist had acceptable convergent validity with measures of overall health (r=0.25–0.58), physical functioning (r=0.22–0.58), emotional distress (r=0.47–0.62) and illness worry (r=0.36–0.55). Acceptability was good with a low number of missing responses to items (<3%). Internal consistency was high (α ≥0.879). BDS score means varied and reflected symptom burden across cohorts (13.03–46.15). We provide normative data for the Danish general population. Conclusions: The BDS checklist total sum score can be used as a measure of symptom burden and FSD illness severity across settings. These findings establish the usefulness of the BDS checklist in clinics and in research, both as a diagnostic screening tool and as an instrument to assess illness severity.